Sepenuh Hati Menggapai Asa Untuk Mewujudkan PTMT Di Sekolah Saat Pandemi Covid - 19 - Sri Kis Untari (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Seeing the many benefits that will be gained from reading a lot. So it is important for teachers and education personnel to read, but not everyone has an interest in reading. Based on the results of observations made by researchers that interest in reading does not go well because teachers and students are not able to focus on reading material. Starting from the things above, the researchers will take a suitable school action to overcome these problems as a solution to make teachers and students active, motivated, and enthusiastic in reading. Therefore, the researchers formulated it into a school action research report entitled: "Efforts to Increase Teachers' and Students' Reading Interest by Expanding the Library Program at SD Negeri Margorejo I/403 Surabaya Odd Semester for the Academic Year 2019/2020". The research was conducted with a two-cycle action mechanism. And based on the results of data analysis, it can be concluded that there is an increase in reading interest through the application of library program extensification for teachers and staff at SD Negeri Margorejo I/403 Surabaya. The increase in reading interest through the implementation of the extensification of the library program for teachers and staff at SD Negeri Margorejo I/403 Surabaya was 22%.